The Association of Aerobic Fitness with Resting State Functional Connectivity and Verbal Learning and Memory in Healthy Young Adults - (:unkn) unknown (My University, 2020)
The beneficial effects of exercise and cardiopulmonary fitness on general health, quality of life, and reduction of mortality are well known in older adults. There is evidence to support the positive effects of exercise and aerobic fitness on psychiatric and neurocognitive function in children, adults, and older adults. Indeed, many studies have explored the positive effects of aerobic fitness on slowing cognitive decline associated with normal and pathological aging. However, comparatively fewer empirical studies in the literature exist to support and understand the effects of aerobic fitness on the developing brain, particularly during adolescence and young adulthood, especially as it relates to resting state functional connectivity during this dynamic stage of development. The current study investigated the association of aerobic fitness on functional connectivity with the left hippocampus in healthy young adults and the degree to which differential resting state functional connectivity is associated with verbal learning and memory. The sample was comprised of healthy young adults with varying degrees of aerobic fitness as part of a larger study of the effects of cardiorespiratory health on neurocognitive performance, brain structure and function. Results of the study indicated that better aerobic fitness is associated with increased functional connectivity to the left parahippocampal gyrus, a region known for its role in working memory and encoding. Results from this study contribute to a better understanding of the factors that may underlie the beneficial effects of exercise on brain health and neurocognition and further offer insights into the value of early preventive health behaviors to reduce the risk of later of cognitive decline and impairment.
Keywords: Aerobic Fitness; Functional Connectivity; Hippocampus; Learning and Memory; Neuropsychology; Parahippocampal Gyrus